The Impact of Waves and Tidal Currents on the Sediment Transport at the Sea Port - Dinh Duc Truong; Doan Quang Tri; Nguyen Cao Don (Salehan Institute of Higher Education, 2021)
Dredged sediments in estuarine and coastal waters can cause sediment transport and water pollutant in marine environment since the sediments are diffused to waterbodies under the influence of wave and flow regimes. As a result, it increases turbidity and enhances sediment deposition at dump sites. In Vietnam, few authors have studied and assessed the environmental impact of dumping and dredged materials to the port areas. This paper combines a coupled spectral wind-wave, hydrodynamic, and sediment transport models in order to study the impact of tide and wave conditions to regional sediment transport patterns at Vung Ang port area in Vietnam. The results for the currents and waves were evaluated and validated using field data. Wind and wave data for the calculated domain are extracted from the WAVEWATCH-III (wave data) and NOAA global climate change models (wind data). The calibration and validation of the MIKE 21/3 showed a high conformity between the observed and simulated data based on the mean absolute error (MAE), the RMSE-observation standard deviation ratio (RSR) and the Percent bias (PBIAS). The MIKE 21/3 sediment transport simulation results showed that the highest suspended sediment concentrations were 2.5-3 g/m3 at the dredging position and the increased concentration along the transport route ranged from 1-1.5 g/m3. The simulation results showed the bed level change of the simulated domain. We found that the suspended sediment diffusion area decreased with the respective depth: Layer 1 (65.5 km2), Layer 2 (45.7 km2), and Layer 3 (37.4 km2). Therefore, the simulation results of the dredged materials activities were significantly affected by the wave and tidal regime on the sediment transport. Doi: 10.28991/cej-2021-03091749 Full Text: PDF